2003
DOI: 10.1046/j.1460-9592.2003.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Supraventricular Tachycardia in the Transplanted Heart:

Abstract: Clinically important supraventricular arrhythmias are occasionally encountered in patients following cardiac transplantation and the use of catheter ablation as a treatment has been reported. The following three cases are described: (1) atrial flutter, including electroanatomic mapping of the donor and recipient components of the right atrium, (2) a mid-septal accessory pathway, and (3) atrioventricular nodal reentrant tachycardia (AVNRT). A Medline database search was performed and articles addressing cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…[7][8][9][10][11][12][13] It should be noted, however, that this particular form of flutter can only occur in transplant patients receiving bi-atrial anastomosis, which has been the standard anastomosis technique for years. More than 97% of patients reported by Ahmari et al 15 had bi-atrial anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] It should be noted, however, that this particular form of flutter can only occur in transplant patients receiving bi-atrial anastomosis, which has been the standard anastomosis technique for years. More than 97% of patients reported by Ahmari et al 15 had bi-atrial anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Successful catheter ablation of atrial flutter in this population has been reported on several occasions by radio-frequency application to the isthmus between the tricuspid valve and the atrial anastomosis adjacent to the inferior vena cava. [7][8][9][10][11][12][13] This is, however, not the usual initial therapeutic modality and such patients are started on antiarrhythmic drugs and anti-coagulation. 14 Herein we report the case of an OHT patient who developed atrial flutter on the surface electrocardiogram (ECG), resistant to conservative management and later underwent basic electrophysiologic (EP) evaluation.…”
mentioning
confidence: 99%
“…1,3,4 SVT due to a pre-existing AP in the donor heart has been reported sporadically in adults, but not in children. 4,5 Approximately 90% of APs in transplanted hearts have been found to be in the left lateral position. 5 Our patient's AP was located in the left anterior position.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Successful radio-frequency catheter ablation (RFA) for AP-mediated tachycardia in transplant patients has been reported in adults as well. 5 Wolff-Parkinson-White (WPW) syndrome in the donor heart is therefore no longer considered an absolute contraindication for OHT in that population. 6 We report the first case of a child who was noted to manifest pre-excitation on his electrocardiogram (ECG) shortly after transplantation, who subsequently underwent successful RFA of an AP.…”
mentioning
confidence: 99%
“…Older data have been limited to arrhythmias resulting from pre-existing donor heart substrate, such as dual AV nodal physiology or AV accessory pathways. 4 Recent data from US transplant centers demonstrate that supraventricular tachycardia affects between 7% and 12% of heart transplant recipients and that complex modification of atrial substrate during cardiac transplant surgery results in both proarrhythmic and antiarrhythmic effects depending on the technique used and other parameters. 5,6 …”
mentioning
confidence: 99%